Student connect portal using web Application - Thimmaiah, Sunil; Sreenivasulu, K N; Bhat, Vinay; Shravanthi; Yashwanth, H S; Nitheesh (2025 International Conference on Knowledge Engineering and Communication Systems (ICKECS), 2025)
Over the past ten years, organizing and taking part in campus events has become very challenging. In order to learn about forthcoming activities, students had to rely on handwritten posters or unofficial word-of-mouth, which frequently resulted in lost chances. To sign up, students had to go to the event organizers in person or get in touch with them by phone or email, which was not only time-consuming but also prone to mistakes. This experience is entirely altered by Connectr. To build this project, we used a framework called React JS, HTML, CSS, JavaScript, MongoDB, and other programming languages. With a straightforward card-based interface, students may now access a variety of coding tools for languages including Java, Python, and JavaScript. Every card offers a concise, visual depiction of a coding topic, making it simple to locate and comprehend. The online registration feature simplifies the sign-up process. Students can register for events directly through the application, which eliminates the need for physical paperwork or lengthy communications. Their registration information is stored in a database, making it easy for administrators to manage and track.